Paving the Way for Tunable Graphene Plasmonic THz Amplifiers - Boubanga-Tombet, Stephane A.; Satou, Akira; Yadav, Deepika; But, Dmitro B.; Knap, Wojciech; Popov, Vyacheslav V.; Gorbenko, Ilya V.; Kachorovskii, Valentin; Otsuji, Taiichi (Frontiers in Physics, 2021)
This paper reviews recent advances in room-temperature coherent amplification of terahertz (THz) radiation in graphene, electrically driven by a dry cell battery. Our study explores THz light-plasmon coupling, light absorption, and amplification using a current-driven graphene-based system because of its excellent room-temperature electrical and optical properties. An efficient method to exploit graphene Dirac plasmons (GDPs) for light generation, and amplification is introduced. This approach is based on current-driven excitation of the GDPs in a dual-grating-gates high mobility graphene-channel field effect transistor (DGG-GFET) structure. The temporal response of the DGG-GFETs to the polarization-managed incident THz pulsation is experimentally observed by using THz time-domain spectroscopy. Their Fourier spectra of the transmitted temporal waveform through the GDPs reveals the device functions (i) resonant absorption at low drain bias voltages below the first threshold level, (ii) perfect transparency between the first and the second threshold drain bias levels, and (iii) resonant amplification beyond the second threshold drain bias voltage. The maximal gain of 9% is obtained by a monolayer graphene at room temperatures, which is four times higher than the quantum limit that is given when THz photons directly interact with electrons. The results pave the way towards tunable graphene plasmonic THz amplifiers.